Mutant enrichment by filtration concentration: a variation for the selection of temperature-conditional heterocaryons - P. J. Applegate; R. E. Nelson; R. L. Metzenberg (Fungal Genetics Reports, 1978)
Mutant enrichment by filtration concentration: a variation for the selection of temperature-conditional heterocaryons